Chlorophyll-a content around the floating needle cage damsite of the Koto Panjang Reservoir, Kampar Regency, Riau Province - Fajar Alamsyah; Eni Sumiarsih; Yuliati (JURNAL MINA SAINS, 2025)
Koto Panjang Reservoir is used as a fish farming site using the Floating Net Cage (KJA) system. The development of KJA in Koto Panjang Reservoir provides economic benefits for the community but also has the potential to cause a decline in water quality. This study aims to analyze the concentration of chlorophyll-a around the reservoir where KJA is located. The survey method was used for observations at 4 stations with 3 replications. The characteristics of the four stations were based on variations in the number of KJA plots: station 1 (60 plots), station 2 (no KJA), station 3 (350 plots), and station 4 (600 plots). Sampling was carried out in the morning from 08.00 to 12.00 WIB. Chlorophyll-a was analyzed using the spectrophotometric method. The concentration of chlorophyll-a in the waters of Koto Panjang Reservoir ranged from 7,693 to 12,927 µg/L, classified as mesotrophic. The highest value was detected at station 4 (12,927 μg/L) and the lowest at station 2 (7,693 μg/L). There was a tendency to increase chlorophyll-A concentrations in line with the increasing number of KJA plots. Water quality in the Koto Panjang Reservoir, based on pH, temperature, clarity, dissolved oxygen, free carbon dioxide, and chlorophyll-a, still supports the life of organisms.